2015
DOI: 10.1186/s13046-015-0208-8
|View full text |Cite
|
Sign up to set email alerts
|

Expression and clinical significance of annexin A2 and human epididymis protein 4 in endometrial carcinoma

Abstract: BackgroundIt is well-known that the treatment and monitoring methods are limited for advanced stage of endometrial carcinoma. Biological molecules with expression changes during tumor progression become potential therapeutic targets for advanced stage endometrial carcinoma. Annexin A2 (ANXA2) has been reported to be overexpressed in recurrent endometrial carcinoma, and the expression of human epididymis protein 4 (HE4) is upregulated in endometrial carcinoma. What’s more, ANXA2 and HE4 interacted in ovarian ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
51
1
4

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(63 citation statements)
references
References 36 publications
7
51
1
4
Order By: Relevance
“…These results indicate that Annexin 2 may be an independent prognostic factor for hepatocellular carcinoma (20). Previous studies have demonstrated that the expression of Annexin A2 is significantly associated with metastasis and poor survival in nasopharyngeal and endometrial carcinoma, bladder cancer and serous ovarian cancer (21)(22)(23)(24). Using a proteomic assay, the present study identified that Annexin A2 was highly expressed in laryngeal carcinoma tissues, consistent with the results of the aforementioned studies.…”
Section: Discussionsupporting
confidence: 80%
“…These results indicate that Annexin 2 may be an independent prognostic factor for hepatocellular carcinoma (20). Previous studies have demonstrated that the expression of Annexin A2 is significantly associated with metastasis and poor survival in nasopharyngeal and endometrial carcinoma, bladder cancer and serous ovarian cancer (21)(22)(23)(24). Using a proteomic assay, the present study identified that Annexin A2 was highly expressed in laryngeal carcinoma tissues, consistent with the results of the aforementioned studies.…”
Section: Discussionsupporting
confidence: 80%
“…Because CA 125 is often elevated in benign conditions or as a result of physiologic changes in premenopausal women, it has not any confirmed role in the early detection of gynecologic cancers. Since abnormal levels of HE4 have been less frequently encountered in benign gynecological conditions HE4 may have increased specificity in differentiating between benign and malignant conditions [2][3][4][5][6][7]. In the present study, we have found that HE4 tissue expression increased in carcinomas, but decreased in intraepithelial neoplasia.…”
Section: Discussionsupporting
confidence: 64%
“…Conversely, HE4 overexpression has not been detected in ovarian mucinous tumors [4][5][6], non-epithelial ovarian cancers, sex cord stromal tumors and germ cell tumors. However overexpression of HE4 has been detected in primary tuba uterina carcinomas and endometrial malignancies [2][3][4][5][6][7]. Among non-gynecological cancers, HE4 expression has been also demonstrated in various subtypes of lung cancer [12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar results were found in the study of Deng et al In their study, HE4 expression in endometrial tissues was significantly higher in EC tissues as compared to the normal endometrium. HE4 was also significantly correlated with the degree of cancer differentiation [24].…”
Section: Discussionmentioning
confidence: 87%